Influence of Parameters the Wall on Reinforced Soil Segmental Walls - Baaziz Salah Eddine; Mellas Mekki (Salehan Institute of Higher Education, 2017)
The behaviour of retaining walls in geosynthetic reinforced soil is complex and requires studies and research to understand the mechanisms of rupture, the behaviour of the reinforcements in the soil and the behaviour of the main elements of the system: reinforcement-wall-soil. Several researches have been done on the use of geosynthetics as backfill massive reinforcement material (experimental studies, numerical analysis, reduced models ...). This parametric study was conducted to investigate the influence of numerical parameters of the wall which confront us in the projects, on the behaviour of walls on reinforced soil segmental walls. A 3.6m high wall is composed of modular blocks of earth sand reinforced with four geogrids layers was modelled. The properties of materials, the wall geometry, and the boundary conditions will be explained later. The finite difference computer program FLAC3D was used in this study. The results of this numerical study allowed to deduce the importance of each parameter of the wall selected for the behaviour of retaining walls in soil reinforced by geogrid. The inclination of wall